Effects of Inoculation With Acinetobacter on Fermentation of Cigar Tobacco Leaves - Zheng, Tianfei; Zhang, Qianying; Wu, Qiaoyin; Li, Dongliang; Wu, Xinying; Li, Pinhe; Zhou, Quanwei; Cai, Wen; Zhang, Juan; Du, Guocheng (Frontiers in Microbiology, 2022)
Metabolic activity of the microbial community greatly affects the quality of cigar tobacco leaves (CTLs). To improve the quality of CTLs, two extrinsic microbes (Acinetobacter sp. 1H8 and Acinetobacter indicus 3B2) were inoculated into CTLs. The quality of CTLs were significantly improved after fermentation. The content of solanone, 6-methyl-5-hepten-2-one, benzeneacetic acid, ethyl ester, cyclohexanone, octanal, acetophenone, and 3,5,5-trimethyl-2-cyclohexen-1-one were significantly increased after inoculated Acinetobacter sp. 1H8. The inoculation of Acinetobacter sp. 1H8 enhanced the normal evolutionary trend of bacterial community. The content of trimethyl-pyrazine, 2,6-dimethyl-pyrazine, and megastigmatrienone were significantly increased after inoculated Acinetobacter indicus 3B2. The inoculation of Acinetobacter indicus 3B2 completely changed the original bacterial community. Network analysis revealed that Acinetobacter was negatively correlated with Aquabacterium, positively correlated with Bacillus, and had significant correlations with many volatile flavor compounds. This work may be helpful for improving fermentation quality by regulating microbial community and gain insight into the microbial ecosystem.